Customary Law during the Covid-19 Pandemic: Supporting Local Government's Policy - Anak Agung Gede Oka Parwata; I Gusti Ngurah Dharma Laksana; A. A. A. N. Harmini; Made Dandy Pranajaya (Jurnal Hukum Prasada, 2023)
The covid-19 pandemic has become a national disaster, therefore the participation of all parties is needed in efforts to handle this disaster. Traditional villages with their customary law have a strategic role in handling Covid-19 starting from managing their territory to distributing social assistance. Through traditional village institutions, the Bali Provincial Government uses local wisdom in increasing community participation and institutions to be actively involved in handling activities and overcoming the impact of Covid-19. This study aims to determine the role of customary law to support government policies in handling Covid-19 in Bali. This study is a descriptive study in which the method used is a normative legal research method, using a statutory approach, a historical approach, a conceptual approach, a philosophical approach, and a case approach. The legal materials used are primary legal materials, secondary materials, and non-legal materials. Based on the research conducted, it was found that Balinese customary law plays a role in supporting government policies in handling Covid-19 in Bali because it is in accordance with the philosophy and principles of customary law adopted by the Balinese indigenous people.